2020
DOI: 10.2147/cmar.s272277
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tobacco Smoke Plays an Important Role in Initiation and Development of Lung Cancer by Promoting the Characteristics of Cancer Stem Cells</p>

Abstract: Lung cancer is one of the most common causes of cancer-related deaths worldwide. Tobacco smoke is the single greatest risk factor of lung cancer. Although enormous progress in understanding the molecular mechanisms by which tobacco smoke leading to lung cancer has been made, the molecular pathogenesis remains largely unclear. Cancer stem cells have been implicated in cancer initiation, development, and drug resistance. In this review, we reviewed the relationship between tobacco smoke and lung cancer, the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…TS is the leading cause of lung cancer and promotes initiation and progression of pulmonary tumorigenesis ( 5 7 , 9 , 48 ). The underlying molecular mechanism of TS causing lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TS is the leading cause of lung cancer and promotes initiation and progression of pulmonary tumorigenesis ( 5 7 , 9 , 48 ). The underlying molecular mechanism of TS causing lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Garnering much research attention, natural compounds were recently reported to produce a suppressive effect on CSC phenotype and related regulatory pathways [ 24 , 32 , 51 ]. Due to the crucial role of CSCs in initiation and maintenance of lung cancer [ 52 ], the results herein revealing anticancer activity of TDB, a bibenzyl extracted from D. ellipsophyllum , against lung CSCs could guide the future investigations and innovations related to CSC-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo evidence suggests that Akt-driven CSC enrichment is mediated by activation of the Wnt/ β -catenin pathway through GSK3 β phosphorylation [ 56 ]. It has been reported that tobacco smoke, an important risk factor for lung cancer, stimulates the Wnt/ β -catenin pathway and enhances the CSC phenotype in lung cancer patients [ 52 ]. Interestingly, small molecules derived from natural products are deemed to possess much therapeutic potential and were even observed to inhibit CSC subpopulations and abolish tumor growth in vivo through inhibition of the Wnt/ β -catenin pathway [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also in a murine model, long-term cigarette smoke exposure in vivo lowered MSCs and HSCs, while increased gene expression related to proliferation, in what is another warning for the use of stem cells from smokers (Siggins et al 2014). Smoke is capable of induce stem cells in the route to lung cancer development (Lu et al 2020). Chronic nicotine exposition modulates epigenome through ROS induction and favors stemness in Hk-2 human kidney epithelial cells, during nicotine-related kidney carcinogenesis (Chang and Singh 2019).…”
Section: Toxic Habits and Diseases In The Donorsmentioning
confidence: 99%